Alternative earning asset alocation beyond loan with government bond; case study of PT. Bank Bukopin,TBK - Jatnika, Okki; Herlanto Anggono, Achmad (The Indonesian Journal of Business Administration, 2019)
Abstract - Bank Bukopin as a bank that focuses on the Small and Medium Enterprise segment, loan is one of its largest revenue stream. The volatility of the economy impacts the Non-Performing Loan of Bank Bukopin, which raise a highest level in December 2017 with 8.54%. This condition makes the management should consider the other earning assets that have a lower risk, to rebalance the portfolio that have a high risk characteristic, such as loan. The forecasting results concludes that the expected Indonesia 10Y Government Bond Yield have a stable growth. Whereas the Interest Income Ratio is decay gradually and aggravated by the Provision Ratio that has a stable growth. It shows that government bond could be an alternative investment option, especially when the bank facing the volatility of economy condition that will impacts the risk of the failure payment from debtor is higher. Loan is still the most priority earning asset of the bank because bank has a responsibility as the intermediary institution, and also loan gives a highest interest income. In other side, Government Bond could be used to rebalance the risk of the earning assets as the less risky investment. FR0046 could be considered as a short-term IDR government bond option and FR0059 as the option for the longer term investment. The simulation on the past financial statement as in December 2017 has shown that the government bond investment can increase the Net Interest Margin from 3.43% into 3.51%.Keywords: Banking, ALMA, Government Bond, Forecasting, ARIMA